Подавляющее большинство: [Сборник] / В. В. Выжутович - Выжутович Валерий Викторович (Лениздат, 1990)
Экземпляры: ф.18 (1990) / Инвентарный номер: 32003 / Цена: / Сис.шифр: 66.3(2)3 / Авт.знак: В 92 / ГРНТИ: 11 / ББК: 66.3(2)3